Dampak Motivasi Kerja, Keseimbangan Kehidupan Kerja, dan Pengalaman Profesional terhadap Kinerja Personel Penerbangan - Widagdo, Rinosa Ari; Wicaksono, Renaldi Hendrasto; Fananda, Valent Akbar (LANCAH: Jurnal Inovasi dan Tren, 2025)
This study examines the impact of work motivation, work-life balance, and professional experience on the performance of aviation personnel. Literature reviews highlight the critical role these factors play in improving work effectiveness and aviation service quality. Work motivation contributes to productivity levels, work-life balance reduces work stress, and professional experience enhances accurate decision-making in emergency situations. The study concludes that managing these three factors is essential for achieving optimal performance.